Statistical Analysis of Cultural Items in the International Chinese Education Network Course Resource Database: Based on the “Chinese Bridge” Delegation Online Experience Platform - Bin, Lang; Numtong, Kanokporn (LEARN Journal: Language Education and Acquisition Research Network, 2024)
This research aims to analyze cultural items in the international Chinese education network course resource database found in the “Chinese Bridge” delegation online experience platform. Data were collected from 878 culture-themed courses implemented by 106 schools (including 64 universities, and 39 vocational colleges, 3 high schools) around China during the year 2023. After utilizing “The Framework of Reference for Chinese Culture and Society in International Chinese Language Education” as classification criteria and applying statistical analysis method, three primary cultural items categories and 27 secondary cultural items categories were showcased. The results showed that schools focused more on society and lifestyles (N=350; 39.9%) and traditional culture (N=301; 34.2%) compared to contemporary China (N=227; 25.9%) in the primary category. The most popular secondary category items were leisure (N=178), art (N=109), cultural heritage (N=102), food (N=83), and inventions (N=59) the above five accounted for more than 60%. These two category levels systematically reflected the synchronic and diachronic characteristics of cultural teaching from supra-regional and regional cultural content. However, two shortcomings were identified, namely homogenization of cultural items presentation and simplification of teaching medium language. The high-frequency recurring cultural items were Chinese tea, Chinese painting, and Tai Chi, which in total were presented in 107 courses and accounted for more than 12%. English is the most important medium language after Chinese, while teaching other languages is relatively lacking. The results of this study also provide valuable insights of improvement strategies proposed by precise learning demands, diversified cultural narration and technology assisted teaching to inspire the schools’ international Chinese education network course resources.